2018
DOI: 10.1111/nph.15477
|View full text |Cite
|
Sign up to set email alerts
|

Functions of stone cells and oleoresin terpenes in the conifer defense syndrome

Abstract: Conifers depend on complex defense systems against herbivores. Stone cells (SC) and oleoresin are physical and chemical defenses of Sitka spruce that have been separately studied in previous work. Weevil oviposit at the tip of the previous year's apical shoot (PYAS). We investigated interactions between weevil larvae and trees in controlled oviposition experiments with resistant (R) and susceptible (S) Sitka spruce. R trees have an abundance of SC in the PYAS cortex. SC are mostly absent in S trees. R trees an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 40 publications
0
70
0
1
Order By: Relevance
“…Conifers have developed a broad array of physical and chemical defensive traits and strategies to reduce the damage caused by a large and diverse community of antagonist organisms (Franceschi et al, 2005;Mason et al, 2019;Whitehill et al, 2019). Among them, resin ducts are the structures that produce and exude the oleoresin (Fahn, 1979), an effective terpenoid-based chemical defense against insects and pathogens (Keeling and Bohlmann, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Conifers have developed a broad array of physical and chemical defensive traits and strategies to reduce the damage caused by a large and diverse community of antagonist organisms (Franceschi et al, 2005;Mason et al, 2019;Whitehill et al, 2019). Among them, resin ducts are the structures that produce and exude the oleoresin (Fahn, 1979), an effective terpenoid-based chemical defense against insects and pathogens (Keeling and Bohlmann, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has highlighted the critical role of specialized diterpenoid metabolism in the pest and pathogen defense of gymnosperms (Keeling and Bohlmann, ; Zi et al ., ; Zerbe and Bohlmann, ; Celedon and Bohlmann, ). In many conifers, and especially in species of pine ( Pinus ), fir ( Abies ) and spruce ( Picea ), abietane‐, pimarane‐ and other labdane‐type diterpene resin acids (DRAs) are key components of the oleoresin defense system that conifers employ to fend off insect pests and fungal pathogens, such as the mountain pine beetle ( Dendroctonus ponderosae ) and associated pathogenic fungi, including the blue stain fungus ( Grosmannia clavigera ) (Keeling and Bohlmann, ; Lah et al ., ; Wang et al ., ; Whitehill et al ., ). By contrast, in Podocarpaceae and Cupressaceae species, including Taiwania , the distinct phenolic labdane‐type diterpenoid ferruginol and related metabolites are major wood constituents (Cox et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Oviposition occurs in the spring and early summer before or around the time of apical bud burst, mostly within the top 5 to 10 cm of the PYAS below the apical bud. In a survey of naturally attacked hybrid spruce (Whitehill et al, ), we found oviposition in the top 1 to 10 cm [6.3 cm (±5.7 cm)] of PYAS, with most (86%) of the eggs in the top 4 cm (Figure ). Eggs take 7 to 10 days for eclosion (Harman, ; Silver, ; Whitehill, Henderson, Strong, et al, ).…”
Section: The Spruce Weevil Life Cycle Defines the Exophase And Endophmentioning
confidence: 80%
“…Neonate larvae emerge from eggs, orient down the apical shoot, and feed on the nutrient rich cortex, phloem, cambium, and outer xylem (Manville, Sahota, Hollmann, & Ibaraki, ). Larvae progress through four instars prior to excavating pupal chambers in the xylem, also called chip cocoons, which are composed of xylem material compacted with oleoresin (Harman, ; Whitehill et al, ; Whitehill, Henderson, Strong, et al, ). Larvae feeding destroys the PYAS phloem and xylem, which transport water and nutrients to the expanding current year apical shoot, as well as the cambium, which is essential for radial growth.…”
Section: The Spruce Weevil Life Cycle Defines the Exophase And Endophmentioning
confidence: 99%
See 1 more Smart Citation